1985
DOI: 10.1007/bf00352081
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic study of 42 cases of Wilson disease

Abstract: This paper reports 42 cases of bone and joint radiographic changes in hepatolenticular degeneration. The cases were proven clinically by ophthalmologic and laboratory study, and their radiographic and joint changes were divided into five groups: no abnormal findings, osteoporosis, osteomalacia (rickets), distinct changes, and miscellaneous. Distinct changes include marginal bone fragments, angulation of carpal bones, squaring of metacarpal heads, and calcification of the joint capsule or tendon insertion. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Hepatolenticular degeneration is a rare inborn disease of defective copper metabolism and is inherited as an autosomal recessive trait1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatolenticular degeneration is a rare inborn disease of defective copper metabolism and is inherited as an autosomal recessive trait1).…”
Section: Discussionmentioning
confidence: 99%
“…Wilson disease is a rare autosomal recessive disorder in which an elevated level of copper accumulates in the liver and other organs, which can eventually result in serious harm to the nervous system, kidneys, and eyes1,2). Wilson disease is present at birth but symptoms generally take years to appear, usually between the ages of four and late teens.…”
mentioning
confidence: 99%
“…Previous studies showed significant proportions of their patients with bone loss from 24[ 7 ] to 78%. [ 8 ] However, their measurements are from observations of simple radiograph, and the subjective examination is considered imprecise to some extent in order to find the presence of demineralization.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the major clinical findings mentioned previously, WD has been reported to be associated with abnormal skeletal manifestations, including arthritis and premature osteoporosis [9]. However, there are limited reports regarding the diagnosis and management of WD and its possible resultant congenital scoliosis.…”
Section: Case Presentationmentioning
confidence: 99%
“…However, congenital scoliosis in WD has not been reported [9,13]. There are no specific guidelines scoliosis operations on patients with WD, but doctors must keep in mind that the progressive liver cirrhosis, neurologic impairment in WD patients could possibly progress to abnormal before surgery.…”
Section: Case Presentationmentioning
confidence: 99%